(untitled) (UUM Journal of Legal Studies, 2024)
Many nations are creating E-courts to simplify court operations. However, religious e-Courts take more work to execute. This study has identified religious court e-Court implementation issues and solutions using Delphi and ANP. It first employed Delphi and a literature review to interview experts face-to-face. Eight judges, I.T. workers, and attorneys from three religious court districts analysed the model using a priority scale with an Analytic Network Process (ANP). The study found that infrastructure or equipment from the application of the e-Court system is the main issue, with a geometric mean of 0.306, followed by Human Resources (0.262), the system (0.219), and regulation (0.213). Improving e-Court system regulation (0.850) and infrastructure were the primary solutions (0.770). This paper details cluster priority solutions and issues. This study suggests that the highest religious court authority focuses on infrastructure, human resources, e-Court operational systems, and associated legislations. The government must adopt the e-Court system and registration laws to encourage more active socialising. The study prioritises e-Court implementation issues in the religious courts of Indonesia.